The Oxford handbook of meaningful work - Yeoman, Ruth, 1964-; Bailey, Catherine (Catherine Truss); Madden, Adrian; Thompson, Marc, 1962- (Oxford : Oxford University Press, 2019)
This handbook examines the concept, practices, and effects of meaningful work in organisations and beyond. Taking an interdisciplinary approach, it reflects diverse scholarly contributions from philosophy, political theory, psychology, sociology, organisational studies, and economics.
The Moral Conditions of Work / Joanna Cuilla -- 'Belonging' and Its Relationship to the Experience of Meaningful Work / Tatjana Schnell, Thomas Höge, Wolfgang G. Weber -- Exploring Work Orientations and Cultural Accounts of Work: Towards a Research Agenda for Examining the Role of Culture in Meaningful Work / Laura Elizabeth Boova, Michael G. Pratt, Doug Lepisto -- Meaning in Life and in Work / Michael F. Steger -- Meanings and Dirty Work: A Study of Refuse Collectors and Street Cleaners / Ruth Simpson, Natasha Slutskaya, Jason Hughes -- Finding Meaning in the Work of Caring / Carol Lynn Pavlish, Roberta Hunt, Hui-wen Sato, Katherine Brown-Sultzman -- Exploring Meaningful Work in the Third Sector / Rebecca Taylor, Silke Roth -- Callings / Ryan Duffy, Jessica England, Bryan J. Dik -- Fostering the Human Spirit: A Positive Ethical Framework for Experiencing Meaningfulness at Work / Douglas R. May, Jiatian Chen, Catherine E. Schwoerer, Matthew D. Deeg -- Leadership and Meaningful Work / Dennis Tourish -- Dignity and Meaningful Work / Norman E. Bowie -- Does My Engagement Matter?: Exploring the Relationship Between Employee Engagement and Meaningful Work in Theory and Practice / Brad Shuck -- Work Through a Gender Lens: More Work and More Sources of Meaningfulness / Heather Hofmeister -- Accounting for Meaningful Work / Matthew Hall -- Cultural, National and Individual Diversity and their Relationship to the Experience of Meaningful Work / Sebastiaan Rothmann, Laura Anne Weiss, Johannes Jacobus Redelinghuys -- Does Corporate Social Responsibility Enhance Meaningful Work? A Multi-Perspective Theoretical Framework / Marjo Lips-Wiersma -- Direct Participation And Meaningful Work: The Implications Of Task Discretion And Organizational Participation / Duncan Gallie -- Bringing Political Economy Back-in: A Comparative Institutionalist Perspective on Meaningful Work / Marc Thompson -- The Meaningful Ci
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 5, 2019).
Keywords: Work -- Psychological aspects; Psychology, Industrial; Work environment; Business ethics; Organizational behavior